Dilution does the trick: role of mixed solvent evaporation in controlling nanoparticle self-assembly - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2014)
An easy and convenient way to prepare superlattices of amine capped gold nanoparticles is presented. It is clearly established that solvent evaporation significantly influences the nature of resulting superlattices and critically governs whether monolayer or multilayer superlattices are formed. More specifically, it is demonstrated that dilution of the nanoparticle dispersion with a similar solvent (but with different vapour pressure) is an expedient handle to control the nature of self-assembly. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Evaporation rate; gold nanoparticles; Nucleation; Self-assembly